Plastic mulching and liming in cambisoles eutricos in Capsicum annum L. Crop in southrern Mexico. - Zetina, Roberto; Uriza, Daniel E (Agronomía Mesoamericana, 2006)
In the south of Veracruz, Mexico, 5000 ha of chili are cultivated annually in acids soils and with a low CIC. The sandy texture of the soil and the low rainfalls in the last three months of the year coincides with the productive stage of plantations established after the heavy rains of june and july. The objective of this study was to evaluate under rain conditions the effect of lime and plastic covering on the acidity of a recently exposed soil to the cultivation and production of “serrano” chili under a high input management system. The experimental design was one of divided parcels with three repetitions: in the big parcels with four dose of liming (0, 0.5, 1 and 3 t/ha of CaCO3) and in the small parcels two plastic coverings (black plastic/ white and plastic black) and a control treatment without covering. The total yield of fruit showed a significant response to the black/white plastic covering and to the interaction lime (1 ton/ha)- (black/ white plastic covering)obtaining increments of the 40% to 82% respectively. The fruit yield did not show a significant response to the lime. Treatments using lime increased the soil pH from 5.2 to 5.6 and the levels of interchangeable bases from 40 to 54 ppm K, 882- 1146 ppm Ca and 205-192 ppm of Mg.